Comparison of restriction endonuclease analysis and phenotypic typing methods for differentiation of Yersinia enterocolitica isolates. - Kapperud, G (1990)
Restriction endonuclease analysis of chromosomal DNA (REAC) was used to study polymorphism in restriction fragment patterns among Yersinia enterocolitica isolates belonging to serogroups O3, O5,27, O8, O9, O13, and O21. Using the enzyme HaeIII and electrophoresis on thin (0.75-mm) vertical 5% polyacrylamide gels, we were able to distinguish at least 22 DNA fragment patterns among the 72 strains examined. The method showed the greatest discriminatory power with regard to serogroup O8, within which as many as 10 different DNA fragment patterns were detected among the 16 strains examined. Compared with O8, serogroups O3 and O9 were relatively homogeneous with regard to REAC patterns. The discriminatory power of the method was compared with H-antigen typing, biotyping, phage typing, antimicrobial susceptibility typing, and restriction enzyme analysis of the virulence plasmid (REAP), by means of Simpson's index of diversity. The results showed that REAC and REAP constitute an effective supplement or alternative to conventional phenotypic methods for tracing epidemiologically related isolates of Y. enterocolitica. Our finding that human and porcine isolates exhibited the same REAC, REAP, and H-antigen patterns provides additional support for the hypothesis that pigs play an important role in the epidemiology of human Y. enterocolitica infection.